Investment, interest, and capital - Hirshleifer, Jack. (Englewood Cliffs, N.J. : Prentice-Hall, 1970)
The book dispels much of the mystery surrounding capital theory. The central contention is that capital theory is not a peculiar branch of economic analysis following its own novel rules, but is rather the generalization of the standard theory of economic choice into the domain of time.
Includes bibliographies.
osc 27/07/2018
Loans
Keywords: Capital; Interest; Investments